1999
DOI: 10.1007/s004410050064
|View full text |Cite
|
Sign up to set email alerts
|

Localisation of phosphatidylethanolamine-binding protein in the brain and other tissues of the rat

Abstract: Phosphatidylethanolamine-binding protein (PEBP) is a highly-conserved 21- to 23-kDa basic protein that shows preferential affinity in vitro for phosphatidylethanolamine. Previous studies have focussed on PEBP in the brain and male reproductive tract where it has been proposed to play a role in membrane biogenesis. In the present more comprehensive study, rat PEBP transcripts and protein have been found to be expressed in all tissues examined, although the levels vary considerably between tissues. However, at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 23 publications
3
31
0
Order By: Relevance
“…Highest levels were seen in testes and brain, followed by liver and kidney. These observations are in good agreement with a prior analysis in rat tissues [12]. No detectable RKIP-1 protein was observed in any tissue from RKIP-1 −/− animals (not shown), with the exception of a low signal in testis (Fig.…”
Section: Expression Of the Rkip Gene Family In The Mousesupporting
confidence: 92%
See 2 more Smart Citations
“…Highest levels were seen in testes and brain, followed by liver and kidney. These observations are in good agreement with a prior analysis in rat tissues [12]. No detectable RKIP-1 protein was observed in any tissue from RKIP-1 −/− animals (not shown), with the exception of a low signal in testis (Fig.…”
Section: Expression Of the Rkip Gene Family In The Mousesupporting
confidence: 92%
“…This phenotype may be evolutionarily reminiscent of the RKIP-1 function previously seen in Drosophila [12] and plants [33]. In Drosophila, RKIP orthologues reside in antennae and olfactory hairs and play a role in odorant binding.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Subsequent studies revealed that PEBP/RKIP is a widely expressed and highly conserved protein that does not share any significant homology with any known protein family, with homologs in, E.Coli, A.thaliana, S.cerevisae, C.elegans, and D. melanogaster, which display a high degree of interspecies similarity [9].…”
Section: Rkipmentioning
confidence: 99%
“…In Drosophila, which expresses at least 7 RKIP isoforms, RKIP/PEBPs were hypothesized to play a role in odorant binding, as the proteins are localized in antennae and secreted into the lumen of olfactory hairs [9].…”
Section: Rkipmentioning
confidence: 99%